The labor system and increasing women’s participation in the labor market, including targeted goals for Vision 2030 - Tammam Abdul Latif Al- Shishakli (International Journal of Law Research and Studies, 2025)
This research project aims to analyze women between the Saudi labor system and the targets of Vision 2030, only women’s participation in the labor market. This study seeks to identify the labor system and women’s participation in the labor market, including the advantages of the targets of Vision 2030, which advance Saudi women’s entry into the field of the labor system and empowerment. The Saudi labor system has undergone fundamental reforms to provide a fair and supportive work environment for women, including: - Equality: Achieving gender equality in wages, employment opportunities, and promotions. - Maternity Rights: Enhancing the rights of working women, such as paid maternity leave, providing rest hours for breastfeeding, and prohibiting unfair dismissal during pregnancy or leave. - Flexible Work: Encouraging flexible work patterns, such as remote work and part-time work, makes it easier for women to balance their careers and families. Vision 2030 initiatives to increase women’s participation and achieve the vision’s goals include several important initiatives: - "Wusool" Initiative: Supports transportation for working women, enabling them to reach their workplace easily and safely. - The "Qara" Initiative: Provides financial support for childcare services, alleviating the burden on working mothers. - Training and Qualification: Providing specialized training programs aimed at developing women’s skills and qualifying them for leadership positions in various sectors, including the judiciary, aviation, and security sectors. - Supporting Entrepreneurship: Encouraging women to start their own businesses and own companies, while providing the necessary facilities.